PRAXIS AND CLASSROOM L2 DEVELOPMENT - Lantolf, James P. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Although most L2 research informed by sociocultural theory (henceforth, SCT) asserts that the fundamental concepts of Vygotsky’s theory are that human mental activity is mediated by socially and culturally created artifacts (see Lantolf & Appel, 1994 and Lantolf, 2000; among others), I believe that the real key to the theory is to be found in the notion of praxis—a notion that Vygotsky appropriated from Marx and which, of course, has its origins in ancient Greek philosophy. For the Greeks, praxis had the general meaning of action as an end itself, whereas for Hegel and Marx it refers to “action which generates an object external to the subject or his [sic] acts” (Sanchez Velazquez, 1977: 1).1 The crucial feature of praxis in its contemporary understanding is the dialectic unity of consciousness (knowledge/theory) and action that results in the creation of an object. In Hegel’s philosophy the object is Ideal, while for Marx, and for Vygotsky, the object is Material. The present article emerges from an on-going project that explores the implications of praxis in Vygotsky’s theory for instructed second language development. In making the case for the importance of praxis and language education, I will first discuss the place of praxis in SCT and will then present some evidence from recently completed large-scale studies of instructed L2 learning by Negueruela (2003) and Yáñez Prieto (2008) that are informed by Vygotsky’s theory. Along the way, I will also briefly consider some other, less robust, though interesting, studies inspired by Vygotsky’s theory of educational praxis. Resumen Aunque la mayoría de las investigaciones sobre la Teoría sociocultural señalan como eje central de la teoría de Vygotsky el hecho de que la actividad mental humana se encuentra mediatizada por artefactos social y culturalmente creados (véase Lantolf & Appel, 1994 y Lantolf, 2000, entre otros), considero que la clave fundamental de esta teoría se encuentra en la noción de praxis –una noción que Vygotsky tomó de Marx y que sin duda tiene su origen en la filosofía clásica griega. Para los griegos, la praxis tenía el significado general de “acción como un fin en sí misma”, mientras que para Hegel y Marx se refiere a “la acción que genera un objeto ajeno al sujeto o sus actos” (Sanchez Velásquez, 1977: 1). La característica fundamental del concepto de praxis en la actualidad es la unidad dialéctica entre la conciencia (conocimiento/teoría) y la acción que resulta de la creación de un objeto. En la filosofía de Hegel el objeto es “ideal” mientras que para Marx y Vygotsky el objeto es “material”. Este artículo surge de una investigación actualmente en curso que explora las implicaciones de la praxis en la teoría de Vygotsky para el desarrollo de la enseñanza de la segunda lengua. Con objeto de resaltar la importancia de la praxis en la enseñanza/aprendizaje de una lengua, me centraré en primer lugar en clarificar el lugar que ocupa la praxis en la Teoría sociocultural y seguidamente presentaré algunos datos tomados de estudios a gran escala llevados a cabo recientemente por Negueruela (2003), Yánez Prieto (2008), y Serrano-Lopez y Poehner (2008) sobre el aprendizaje de una L2, y enmarcados en la teoría de Vygotsky. Del mismo modo me referiré a otros estudios –menos sólidos aunque igualmente interesantes- inspirados en la teoría de Vygotsky.